(untitled) (Research, Society and Development, 2021)
This article aims to reflect on questions about education and culture in the Amazon, under an anthropological and interdisciplinary bias. This is a bibliographic study. In this sense, the proposal is to think of education and culture as dimensions of the social process, considering the emergence of new technologies and their interactions with current local and global cultures. The reflection exposed here, at the same time, has the purposes to think about the role of institutional education and popular education in the context of social relations that permeate school-society / teachers-students. Therefore, the readings of an interdisciplinary approach, provided an approximation of the Amazonian school daily life and its interactions in the midst of situations that involve education processes and their transformations in the globalized world.